PEMETAAN POTENSI DESA DALAM UPAYA MENGEMBANGKAN DESA WISATA DI DESA PENGUJAN KABUPATEN BINTAN - Sri Ruwanti; Nurhasanah S (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Law No. 6, 2014 on Villages gives authority to Villages in the field of governance, implementation of development, community development, and empowerment of Village communities based on community initiatives, rights of origin, and Village customs. Efforts to implement Village development that have an impact on improving the welfare of the Village community can be realized through development strategies, one of which is through the event of a Desa Wisata (DEWI). Pengujan Village is one of the villages in Teluk Bintan District, Bintan Regency which expected to develop a Tourism Village. The purpose of this Community Service activity is to carry out potential village mapping. The method used is through the Forum Group Discussion (FGD) and observation. The results of this activity are in the form of a village tourism map and a mapping of village potential from social, economic, and environmental aspects which expected to be useful for formulating development strategies, especially the management of Tourism Villages.